Locating host plants via orientation to standing visual targets has dispersal benefits for the monophagous leaf beetle Ambrostoma quadriimpressum - Sun, Fan; Bao, Chao; Jing, Tian-Zhong (Entomologia experimentalis et applicata, 2016)
The highly specialized chrysomelid Ambrostoma quadriimpressum Motschulsky (Coleoptera: Chrysomelidae) is strictly monophagous on elm trees, Ulmus pumila L. (Ulmaceae) and a few of its close relatives. In order to elucidate how the adult beetles find their host plants, we performed both choice and no‐choice arena field experiments to examine their spatial maneuvering under seminatural conditions. In the no‐choice experiments, three treatments were tested in which individual beetles in thanatosis were released in the vicinity of a host plant, in which they were released facing (1) toward the host, (2) away from the host but toward a black paper column, or (3) away from the host with no standing target in view. Videorecordings of the beetles’ walking tracks showed that a standing visual target in field of vision strongly influenced their behavior. The host plant and black paper column equally attracted beetles released facing toward them. In choice experiments, the beetles randomly moved to both host and non‐host plants, as well as to the host plant and the black paper column, indicating that they do not discriminate host plants from a distance. The results suggest that this monophagous beetle locates host plants via orientation to standing visual targets. The results also indicate that the beetle encounters hosts by chance. The benefit of such a host‐finding mechanism in light of dispersion and emigration of the beetle is discussed.